ГАЗЕТНАЯ ЗАМЕТКА ИЛИ ЭСТЕТИЧЕСКИЙ ОБЪЕКТ? ФЕЛЬЕТОН КАК ЛИТЕР АТУРНЫЙ ЖАНР - Прохоров, Георгий (Przegląd Rusycystyczny, 2016)
NEWSPAPER INFORMATION OR FICTIONAL TEXT? FEUILLETON AS A LITERARY GENRE S u m m a r y In focus of our article are approaches to poetics of feuilleton, what is a kind of literary genre merging two sides of a boundary of literature and journalism. Such texts represent a mundane reality like newspapers, but also they represent fictional vision of an author, like ordinary literature. Studying some pre-Soviet feuilletons — St. Petersburg Dreams in Verse and Prose and fragments of A Writer’s Diary by Fyodor Dostoevsky, we dissect how fictional and aesthetic intention emerges beneath initial journalistic task. We trace how author’s interest fluctuate from an explanation of facts by options of logic to mimetic imaging of how persons can live and act in the world. Feuilletons base upon a deep and total personalization, so that ‘real world’ facts appear as relations between different persons.